2008
DOI: 10.1007/s10439-008-9495-y
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment-Based Model of Vein Graft Remodeling Induced by Shear Stress

Abstract: Vein graft intimal hyperplasia induced by shear stress is considered to be one of the major causes of vein graft failure. We have developed a mathematical model of vein graft intimal hyperplasia induced by shear stress based on experimental data. Intimal thickness and the rate of intimal thickness change are expressed as functions of shear stress and time. The model coefficients are derived from animal experiments where bilateral rabbit carotid vein grafts are exposed to different shear stress levels. Morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The few available studies concentrate on short term responses [16,17,40,45]. Nonetheless, parallels can be drawn between the current results and observed trends in arterial G&R in hypertension (which is a modest pressure perturbation relative to that considered here).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The few available studies concentrate on short term responses [16,17,40,45]. Nonetheless, parallels can be drawn between the current results and observed trends in arterial G&R in hypertension (which is a modest pressure perturbation relative to that considered here).…”
Section: Discussionsupporting
confidence: 67%
“…Some previous attempts at modeling vein graft adaptations have prescribed changes in geometry as functions of time and stress [17,43]. In contrast, the current model makes changes in geometry, structure, and composition of the vessel a consequence of the cell mediated G&R that tries to restore homeostatic stresses; that is, the results of the present model are "emergent."…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As an undesirable effect of the changed conditions, the patency of the graft may be substantially compromised by an intimal hyperplasia or thrombosis (Fitzgibbon et al, 1996;Hwang et al, 2012). Much work is now being done to deepen our knowledge of the mechanobiology of graft remodeling, but this process is still not completely understood (Tran-Son-Tay et al, 2008;Hwang et al, 2012;2013;Sassani et al, 2013). The adaptation to the changed conditions leads not only to a change in the diameter and thickness of the graft wall, but also to a changed internal structure and thus a change in the constitutive equation (Hwang et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Tran-Son-Tay et al 18 previously showed that SVG walls are particularly susceptible to remodeling early after CABG and that hyperplasia growth becomes slower over time. Based on the above and the findings of the current study, the use of β-blockers early after CABG may be particularly important in keeping with current clinical guidelines, supporting their use to prevent adverse events in the postoperative period.…”
Section: β-Blockers and Svg Remodelingmentioning
confidence: 99%